Linguistic Discrimination Toward Roma: Can Intergroup Threat Enhance Bias?. (June 2018) - Albarello, Flavia; Rubini, Monica
This study tested whether intergroup threat enhances prejudice and discrimination toward the highly discriminated out-group of Roma. An implicit measure of linguistic discrimination, namely language abstraction of terms used in Roma descriptions, and an explicit measure of affective prejudice, that is, feelings thermometer, were employed. The relation between implicit and explicit discrimination was also analyzed. Threat enhanced linguistic derogation and affective prejudice toward Roma. Linguistic abstraction mediated threat's effect on affective prejudice. The implications of the findings were discussed with reference to the role of language in shaping intergroup relations and social exclusion.